#### Answer

P(-1) = 9

#### Work Step by Step

P(x) = 5$x^{4}$ - 3$x^{2}$ + 7
///Plug in -1 for x everywhere
P(-1) = 5($-1^{4}$) - 3($-1^{2}$) + 7
P(-1) = 5(1) - 3(1) + 7
P(-1) = 5 - 3 + 7
P(-1) = 9

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

P(-1) = 9

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.